Beiträge zur Insektenfauna der DDR: Lepidoptera - Tortricidae (Tribus Archipini). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1990)
On the basis of the evaluation of collections and literature and the author's collecting, 38 species of the tribe Archipini were established for the GDR. On order to facilitate determination, the wings are shown in illustrations, and for Aphelia unitata and A. paleana also the genital apparatus.